Teaching method reading and comprehension of the text “Waves” (Sóng) by Xuân Quỳnh in the high school - Mai Hương, Nguyễn Thị (Journal of Education, Linguistics, Literature, and Art, 2024)
Literature is an important subject in school education. Maxim Gorky, a famous Russian writer, once said that "Literature is human science." Studying literature is learning how to be human. Literature provides learners with knowledge about life and the hidden things in the human soul. Moreover, literature today also directly affects human emotions, making people's lives more meaningful, optimistic, and loving. Each essay, poem, and literary work in the general education program is a moral education lesson for students. It contributes to the development and perfection of students' personalities. In order to achieve effective teaching of Literature for students, teachers need to proactively change their teaching methods and mindset. With the topic of "Teaching method for reading and comprehension of the text Waves by Xuân Quỳnh in the high school" (Literature for class 11), we want to introduce a scientific and appropriate teaching method for students to receive and memorize knowledge. At the same time, we also hope that the topic will contribute a small part to the study of lyric texts as a useful reference material for teachers and students.